Knife Edge - Blackman M. Malorie (London, Gorgi Books, 2005)
Sephy is a Cross, one of the privileged in a society where the ruling Crosses treat the pale-skinned noughts as inferiors. But her baby daughter has a nought father - Callum. Eaten up with bitterness, Callum`s brother Jude, blames Sephy for the terrible losses his family has suffered. Now Jude`s life rests on a knife edge.